Refugees and the Ethics of Forced Displacement - Parekh, Serena (Taylor & Francis, 2016)
This book is a philosophical analysis of the ethical treatment of refugees and stateless people, a group of people who, though extremely important politically, have been greatly under theorized philosophically. The limited philosophical discussion of refugees by philosophers focuses narrowly on the question of whether or not we, as members of Western states, have moral obligations to admit refugees into our countries. This book reframes this debate and shows why it is important to think ethically about people who will never be resettled and who live for prolonged periods outside of all political communities. Parekh shows why philosophers ought to be concerned with ethical norms that will help stateless people mitigate the harms of statelessness even while they remain formally excluded from states.